The rise of the BJP : the making of the world's largest political party - Yadav, Bhupender, 1969-; Patnaik, Ila (Gurugram, Haryana, India : Penguin/Viking, an imprint of Penguin Random House, 2022)
The Bharatiya Janata Party is an idea that was seeded into the minds of nationalist Jana Sangh leaders when they began to envision India after Independence. Much like the very core the freedom struggle was built on, they saw India as a demographically, culturally and historically cohesive and unified nation - as Bharat. In this book, senior BJP leader and cabinet minister Bhupender Yadav and leading economist Ila Patnaik come together to trace the BJP's journey from its humble roots, through ups and downs and to eventually getting 303 seats in Lok Sabha in 2019 and becoming the world's largest political party. While focusing on the larger economics and political story, the book encapsulates many smaller, yet hugely significant stories of individuals and incidents, which brought the BJP to where it stands now. For the first time ever, The Rise of the BJP, tells us the inside story of how one of the most powerful political parties makes decisions, implements ideas and executes policy. Meticulously researched and immensely readable, the book shows us how the BJP fought competing ideologies, political assaults and catapulted to the centre stage of national politics. - Publisher.
Preface -- 1. The Jana Sangh -- 2. The Jana Sangh after Mookerjee -- 3. A party is born -- 4. Decade of growth (1986-1996) -- 5. BJP in government (1996-2004) -- 6. The loss of 2004 -- 7. Building the party (2004-2008) -- 8. The road to resurgence (2009-2014) -- 9. Working in unison: party and government (2014) -- 10. Expansion and outreach (2015) -- 11. Winning the states (2016-2018) -- 12. The campaign for Lok Sabha 2019 -- Epilogue -- Notes -- Index.
Includes bibliographical references.
Also available as an ebook.
Keywords: Bharatiya Janata Party -- History; Bharatiya Janata Party; Since 1947; Political parties -- India; Politics and government; India -- Politics and government -- 1947-; Inde -- Politique et gouvernement -- 1947-; India; History